Vegetable fiber as reinforcing elements for cement based composite in housing applications - A Brazilian experience - Da Costa Correia, Viviane; Santos, Sergio Francisco [UNESP]; Savastano, Holmer (EDP Sciences, 2018)
Vegetable fibers are a hierarchical structure material in the macro, micro and nanometric scales that have been used as reinforcement in cementitious materials. In nanoscale, the nanofibrillated cellulose has the advantage of having good mechanical performance and high specific surface, which contributes to improve the adhesion between fiber and matrix. In hybrid reinforcement, with micro and nanofibers, nanofibrillated cellulose forms bonding with the matrix and acts as stress transfer bridges in the nano-cracking with corresponding strengthening of the cementitious composite. Processing has a strong influence on performance of the fiber cement composite. Two fabrication methods were evaluated: (i) slurry dewatering followed by pressing and (ii) extrusion. The extrusion process strongly depends on the rheological characteristics of the fresh cement material but it can better organize the microstructure of the fiber cement due to the partial orientation of the fibers in the extruder direction. Curing process also plays a key role in the performance of the final product. Accelerated carbonation at early age is a promising technology and a strategy to mitigate the durability problems with the composite materials; it decreases porosity, promotes a higher density in the interface guarantying a good fiber-matrix adhesion and a better mechanical behavior. Alternative MgO-SiO2 clinker free binder is also presented as a suitable alternative to cementitious products reinforced with cellulosic pulps. Finally, mechanical behavior of fiber cement under flexural loading is evaluated by modulus of rupture, fracture toughness, the initial crack growth resistance in cement matrix, and fracture energy that is obtained to evaluate the influence of toughening mechanisms promoted by fibers, such as pullout and bridging, on the mechanical performance of the composites. Degradation during the service life is also crucial for the evaluation of the durability of the resulting materials and components in real applications exposed to different environmental conditions as roofing, partitioning or ceiling elements. It can be concluded that more sustainable and high performance components based on engineered natural raw materials for civil construction can bring valuable contributions for the affordable housing in particular to developing region.